KAJIAN KESIAPAN MASYARAKAT KAWASAN PANTAI TANJUNG KELAYANG SEBAGAI MASYARAKAT WISATA BAGI PENGEMBANGAN PARIWISATA BELITUNG - Widyastuti, Dida Hernandini Maretta; Rosyidie, Arief (Jurnal Ilmiah Pariwisata, 2017)
Belitung is one of the regencies in Bangka Belitung Province that has quite large mineral resources of tin mining and has provided a lot of benefit to Belitung Regency for hundreds years. However, these unsustainable mineral resources reserves dwindling and has impact in environmental damage. Meanwhile, Belitung also has the potential of nature tourism that is very unique. The tourism sector is expected to replace the previously development bases of Belitung regency in mining sector, which in turn could improve the welfare of society. This policy also supported by determination Tanjung Kelayang area as a National Tourism Strategic Area. The acceleration of tourism development has not been balanced yet by the readiness of the community, both of as a host and as a business tourism operator. This study aims to assess the community readiness take on tourism-based development. Identifying the readiness both of as the host, which encompass cognitive, affective a nd conative aspects as well as tourism businesses operators, which encompass cognitive, functional and social competencies. Based on the results of analysis, known that the local community of Tanjung Kelayang area still not ready either as a host or as a tourism business operators. Miners mindset for hundreds years has been deeply embedded in the public mindset. However, along with the accelerating of tourism development, the community began to transform into the tourism community. Moreover, some people’s respond is to begin changing their professions to the tourism sector, despite of not continuous and only rely on a drop of skills. Based on the results of analysis, also noted that the community’s competencies as a tourism business operators are still very low level, especially of cognitive competencies and functional competencies, which indicates the low competitiveness of Belitung tourism. People who started to switch the professions in tourism sector, currently do not have the educational background of tourism and neither any formal tourism training yet. All the expertise and skills that they have only rely on the expertise and skills that has learned autodidact and hereditary. Therefore, formed the Local Working Group (LWG) as an opinion leader whose role is to foster and to assist the communities, and also to mediate the various elements of tourism actors in order to collaborate in the development of tourism.